Validation of the personal suicide stigma questionnaire among adolescents with suicide attempts in mainland China - Wang, Xiaoning; Miao, Qunfang; Wang, Jiannv; Qiu, Lingjing; Zhang, Jinsheng; Li, Peiqing; Huang, Yaoyao (Frontiers in Psychiatry, 2024)
The study aimed to translate and culturally adapt the personal suicide stigma questionnaire (PSSQ) into simplified Chinese and evaluate its psychometric properties among adolescent s who have attempted suicide in mainland China.Following Brislin's translation model and using purposive sampling, we surveyed 440 adole scents who had attempted suicide at Hangzhou Seventh People's Hospital in Zhejiang Prov ince, China. Content validity was determined by a panel of experts, and the construct vali dity of the scale was assessed using exploratory factor analysis (EFA), confirmatory factor analysis (CFA), convergent validity, and discriminant validity. Reliability analysis was eval uated using Cronbach's α coefficient, test-retest reliability, and half-split reliability.The Chinese version of the PSSQ consists of 3 dimensions and 14 items. After two round s of expert consultation, the item-content validity index for all items exceeded 0.70, and t he scale-content validity index exceeded 0.90. EFA extracted three factors and retained all 14 items. The CFA indicators demonstrated a good fit. The Cronbach's α coefficient of th e scale was 0.880, the half-split reliability was 0.681, and the test-retest reliability was 0.8 62. It is evident that the PSSQ and its subscales demonstrate stable structural validity and good internal consistency in measuring self-stigma among individuals with suicidal tendenci es, indicating that the PSSQ is a reliable tool for assessing the degree of personal stigma in Chinese adolescents who have attempted suicide.This study ensured the linguistic and cultural appropriateness of the Chinese version of the PSSQ through cross-cultural adaptation and validation of its reliability and validity, thereb y enhancing the accuracy and reliability of assessing personal stigma among Chinese adole scents who have attempted suicide. The validation of the Chinese version of the scale not only enriches the research tools available for studying personal stigma related to suicide in Mainland China, but also provides a reliable quantitative tool for future research on the psychological states of individuals who have attempted suicide, the impact of stigma, and the effectiveness of interventions.